Spontaneous Canalith Jam and Apogeotropic Horizontal Canal Benign Paroxysmal Positional Vertigo: Considerations on a Particular Case Mimicking an Acute Vestibular Deficit. Issue 9 (October 2018) - Comacchio, Francesco; Poletto, Elisabetta; Mion, Marta
Abstract : Objective: Canalith jam refers to a condition caused by an otolithic clump blocked inside a semicircular canal, generally provoked by canalith repositioning procedure. We describe the first case of spontaneous canalith jam mimicking an acute vestibular deficit. Patient: We report the case of an 82-year-old woman who suffered a sudden episode of persistent rotational vertigo with nausea and vomiting, not provoked by head movements. Interventions: Videonystagmography revealed a horizontal right-beating spontaneous nystagmus, inhibited by visual fixation. Surprisingly, the positional test showed a direction changing apogeotropic horizontal nystagmus weaker in the left side, compatible with a left side horizontal canal canalolithiasis of the apogetropic type. Returning to the sitting position, a spontaneous nystagmus was observed again, not tilt sensitive. A left side caloric paresis was found. Results: After performing liberatory maneuvers, the spontaneous nystagmus disappeared and a horizontal canal benign paroxysmal positional vertigo of geotropic type was documented. The canal paresis also disappeared. Conclusions: Canalith jam is rarely described and is overall observed as a repositioning manoeuvre complication, not as a mimicker of a vestibular neuritis. Furthermore, our case represents the first observation of a recurrent canalith jam and apogeotropic variant of horizontal canal benign paroxysmal positional vertigo.